Evaluasi Metode Meyerhof dan Schmertmann–Nottingham Berbasis CPT untuk Meningkatkan Reliabilitas Estimasi Qu - Jarmiati Pinkan Ladiyana; Agata Iwan Candra (Jurnal Konstruksi, 2026)
Differences in pile dimensions and layered soil geotechnical characteristics have the potential to reduce the accuracy of foundation bearing capacity estimation; therefore, a more accurate and verified calculation approach is required. This study evaluates the ultimate bearing capacity (Qu) based on Cone Penetration Test (CPT) data by comparing the Meyerhof method and the Schmertmann–Nottingham method for piles with diameters of 20 cm, 40 cm, and 60 cm at two test locations (S1 and S2). The evaluation results indicate that the Schmertmann–Nottingham method produces higher Qu values than the Meyerhof method for all pile diameter variations, with a very strong linear relationship between pile diameter and Qu, as indicated by the coefficient of determination (R2 >= 0.97). Statistical validation using ANOVA proves that both the calculation method and pile diameter have a significant effect on Qu, with pile diameter being the dominant factor in increasing the sensitivity and reliability of ultimate bearing capacity estimation based on CPT data.